Photodegradation of lincomycin and diazepam in sewage treatment plant effluent by photo-Fenton process - Bautitz, Ivonete Rossi [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Elsevier B.V., 2010)
First, the effect of ferrioxalate or iron nitrate on the photo-Fenton degradation efficiency of the pharmaceuticals lincomycin (LCM) and diazepam (DZP) was evaluated. The degradation of both pharmaceuticals was improved in the presence of ferrioxalate in relation to Fe(NO(3)), either under black-light or solar irradiation. The degradation of the pharmaceuticals was then evaluated when present in an effluent from sewage treatment plant (STP) under black-light irradiation. Pharmaceuticals oxidation was not influenced by the matrix, since very similar results were obtained when compared to the experiments carried out in distilled water. However, DOC removal was slightly affected by the matrix, due probably to the generation of recalcitrant intermediates during effluent photodegradation and to the high content of inorganic carbon of STP effluent. Even so, high DOC removal percentages were achieved, 65% for lincomycin and 80% for diazepam after 60 min irradiation. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diazepam; Lincomycin; Photo-Fenton; Sewage treatment plant